Análisis del comercio internacional de Colombia entre los años 2015 a 2021 - Tintinago Tovar, Jorge Luis; Caicedo Rodriguez, Karol Juliana (Universidad Antonio Nariño, 2023)
Analyze the behavior of Colombia's International Trade between the years 2015 to 2021